Bacteriorhodopsin mutants containing single tyrosine to phenylalanine substitutions are all active in proton translocation. - Mogi, T (1987)
To study the possible role of the tyrosine residues in proton translocation by bacteriorhodopsin, we have replaced these residues individually by phenylalanine. The required codon changes were introduced in the bacterioopsin gene by replacement of appropriate restriction fragments by synthetic counterparts containing the desired nucleotide changes. The denatured opsin polypeptides obtained by expression of the mutant genes in Escherichia coli were purified and treated with a mixture of detergents, phospholipids, and retinal in a previously established renaturation procedure. All of the mutant proteins folded to regenerate bacteriorhodopsin-like chromophores. Three mutants with tyrosine to phenylalanine substitutions at positions 57, 83, and 185 regenerated the chromophore more slowly than the wild-type protein, and two of these mutants, Phe-57 and -83, showed slightly blue-shifted chromophores. When reconstituted into liposomes all of the mutant proteins with single Tyr----Phe substitutions pumped protons at rates and levels comparable to those of the wild-type bacteriorhodopsin. We conclude that single substitutions of tyrosine by phenylalanine do not affect folding, retinal binding, or light-dependent proton pumping in bacteriorhodopsin.